2002
DOI: 10.1107/s0909049502008579
|View full text |Cite
|
Sign up to set email alerts
|

Radiation damage of protein crystals at cryogenic temperatures between 40 K and 150 K

Abstract: X-ray radiation damage of lysozyme single crystals by an intense monochromatic beam from the Advanced Photon Source is studied at cryogenic temperatures between 40 K and 150 K. The results con®rm that primary radiation damage is both linearly dependent on the X-ray dose and independent of temperature. The upper limit for the primary radiation damage observed in our previous study [Teng & Moffat (2000), J. Synchrotron Rad. 7, 313±317] holds over the wider temperature range of this study. The X-ray diffraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 14 publications
7
51
0
Order By: Relevance
“…Using the radiationdamage metric of Kmetko et al (2006), we examined 49 thaumatin crystals to determine the radiation-sensitivity at 11 temperatures from 300 to 100 K. Our results agree with previous studies at 300 and 100 K and indicate that most of the reduction in sensitivity on cooling from 300 to 100 K occurs above 200 K. These results are consistent with previous reports on the temperature-dependence of global damage (Teng & Moffat, 2002;Borek et al, 2007;Meents et al, 2010). We model radiation damage as a thermally activated process with a large barrier and a small barrier.…”
Section: Radiation-damage Mechanismssupporting
confidence: 82%
“…Using the radiationdamage metric of Kmetko et al (2006), we examined 49 thaumatin crystals to determine the radiation-sensitivity at 11 temperatures from 300 to 100 K. Our results agree with previous studies at 300 and 100 K and indicate that most of the reduction in sensitivity on cooling from 300 to 100 K occurs above 200 K. These results are consistent with previous reports on the temperature-dependence of global damage (Teng & Moffat, 2002;Borek et al, 2007;Meents et al, 2010). We model radiation damage as a thermally activated process with a large barrier and a small barrier.…”
Section: Radiation-damage Mechanismssupporting
confidence: 82%
“…The former results from the interaction of an X-ray photon with atoms in the sample, leading to the ejection of a highly energetic electron as a result of the photoelectric effect, which is the dominant inelastic event at the photon energies used in macromolecular crystallography (Murray et al, 2005). Primary radiation damage is temperature-independent (Teng & Moffat, 2002). Secondary damage arises from the many secondary radicals created by the primary photoelectron.…”
Section: Protein Structures At Various Cryo-temperaturesmentioning
confidence: 99%
“…In an important advance, it was shown that radiation damage could be mitigated by cryogenic vitrification of protein crystals (Hope 1988). At temperatures of 100 K, crystals become almost (but not quite) immortal (Garman & Schneider 1997;Teng & Moffat 2002;Meents et al 2010). Control studies with small proteins showed that in general cryo-cooling changes neither the overall structure nor details of the functional sites but that the dynamic properties of a protein may be changed (Rasmussen et al 1992).…”
Section: Radiation Damage and Cryo-crystallographymentioning
confidence: 99%